Magnetic sheet and method for manufacturing the same

JP7609195B2Active Publication Date: 2025-01-07PROTERIAL LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023083520
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-21
Filing Date
2023-05-19
Publication Date
2025-01-07
Estimated Expiration
2040-05-21

AI Technical Summary

Benefits of technology

【0009】 本開示によれば、合金薄帯を複数に分割する外力の大きさを小さくすること、分割された合金薄帯の平面状態を良好とすること、磁気特性の経時変化を抑制すること、の少なくとも一つが可能な合金薄帯積層体の製造方法及び上記合金薄帯積層体の製造装置が提供される。例えば、本開示によれば、クラックを形成するために合金薄帯に加える外力の大きさを小さくすることができ、クラックが形成された合金薄帯の平面状態を良好とすることができる。これにより、クラックが形成された合金薄帯を積層して、合金薄帯積層体を構成したとき、平面状態が良好な合金薄帯積層体を得ることができる。また、合金薄帯積層体の磁気特性の経時変化を抑制することができる。また、磁性シートに適用可能な合金薄帯積層体を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007609195000002
    Figure 0007609195000002
  • Figure 0007609195000003
    Figure 0007609195000003
  • Figure 0007609195000004
    Figure 0007609195000004
Patent Text Reader

Abstract

To provide a method for producing an alloy ribbon laminate, capable of at least one of reducing the magnitude of an external force that divides an alloy ribbon into a plurality of pieces, preparing a divided alloy ribbon in a favorably flat state, and suppressing changes with time in magnetic properties.SOLUTION: A method for producing an alloy ribbon laminate includes the steps of: forming cracks in an alloy ribbon of a first laminated member including an adhesive layer and the alloy ribbon by directly applying an external force to the alloy ribbon and obtaining a first laminate including the adhesive layer and the alloy ribbon with the cracks formed therein; forming cracks in an alloy ribbon of a second laminated member including an adhesive layer and the alloy ribbon by directly applying an external force to the alloy ribbon and obtaining at least one second laminate including the adhesive layer and the alloy ribbon with the cracks formed therein; and laminating the at least one second laminate on the first laminate and obtaining an alloy ribbon laminate in which the adhesive layer and the alloy ribbon with the cracks formed therein are alternately laminated.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a magnetic sheet and a method for manufacturing a magnetic sheet. [Background technology]

[0002] In recent years, electronic devices such as smartphones, tablet-type information terminals, and mobile phones have rapidly become widespread. In particular, mobile phones (e.g., smartphones), web terminals, music players, and the like are required to be able to be used continuously for long periods of time in order to be convenient as portable devices. These small portable devices use secondary batteries such as lithium-ion batteries as their power source. There are two methods for charging these secondary batteries: a contact charging method in which charging is performed by directly contacting an electrode on the power receiving side with an electrode on the power supplying side, and a non-contact charging method in which transmission coils are provided on both the power supplying side and the power receiving side, and charging is performed by power transmission using electromagnetic induction. Since the non-contact charging method does not require electrodes for directly contacting the power supplying device and the power receiving device, it is also possible to charge different power receiving devices using the same power supplying device. In addition, the non-contact charging method is a technology that can be used not only in portable devices, but also in other electronic devices, electric vehicles, drones, and the like.

[0003] In the non-contact charging method, the magnetic flux generated in the primary transmission coil of the power supply device generates an electromotive force in the secondary transmission coil of the power receiving device through the housings of the power supply device and the power receiving device, thereby supplying power. To obtain high power transmission efficiency, a magnetic sheet is installed as a coil yoke on the side of the transmission coil opposite the contact surface between the power supply device and the power receiving device. Such a magnetic sheet has the following functions: The first role is as a magnetic shielding material. For example, when leakage magnetic flux generated during charging of a non-contact charging device flows to other components such as metal members that make up the secondary battery, these components generate heat due to eddy currents. The magnetic sheet can suppress this heat generation by acting as a magnetic shielding material. The second role of the magnetic sheet is to act as a yoke member that returns the magnetic flux generated in the coil during charging.

[0004] Conventionally, ferrite materials have been the mainstream soft magnetic materials used in magnetic sheets for contactless charging devices. However, recently, as shown in JP 2008-112830 A, thin alloy ribbons made of soft magnetic materials such as amorphous alloys and nanocrystalline alloys have also begun to be used. JP 2008-112830 A discloses a method for manufacturing a magnetic sheet, which includes a step of forming a magnetic sheet by adhering a thin magnetic material (alloy ribbon) on a sheet base material via an adhesive layer, and a step of dividing the alloy ribbon into a plurality of pieces by applying an external force while maintaining the alloy ribbon adhered to the sheet base material in order to improve the Q value or reduce eddy current loss. JP 2008-112830 A also discloses that by applying an external force to the alloy ribbon to divide it into a plurality of pieces, the Q value can be improved when the magnetic sheet is used as a magnetic material for an inductor, for example. JP 2008-112830 A also discloses that when the magnetic sheet is used as a magnetic material for a magnetic shield, the current path of the alloy ribbon can be divided to reduce eddy current loss. JP 2008-112830 A also discloses that when the alloy ribbon is divided into a plurality of pieces, the divided magnetic material pieces have an area of ​​0.01 mm 2 More than 25mm 2 It is disclosed that the following ranges are preferable:

[0005] Furthermore, JP2015-505166A discloses, as an example of a method for manufacturing a magnetic sheet, the application of the following two steps: 1) a step of attaching a protective film and a double-sided tape having a release film formed on the exposed surface to both sides of a thin-film magnetic sheet (alloy ribbon) consisting of at least one layer of amorphous ribbon to form a laminated sheet; and 2) a step of subjecting the laminated sheet to a flake treatment to divide the alloy ribbon into a large number of small pieces. It is further disclosed that the subsequent step is 3) laminating the laminated sheet subjected to the flake treatment to flatten and slim the laminated sheet, and to fill the gaps between the numerous strips with a part of the first and second adhesive layers provided on the protective film and the double-sided tape to provide isolation. The sheet is flattened and slimmed down by the step 3). Summary of the Invention [Problem to be solved by the invention]

[0006] When a magnetic sheet using multiple divided alloy ribbons is used in a non-contact charging device, magnetic permeability is often used as a substitute for magnetic properties to quantify the state of division. Normally, a magnetic sheet with an AC relative magnetic permeability μr of 100 to 2000 at 128 kHz is required. To obtain a magnetic sheet with this magnetic permeability value, the alloy ribbon needs to be finely divided at intervals of about 1 mm. However, as in JP2015-505166A, when an external force is applied through a resin film to finely divide the alloy ribbon inside, the resin film of the magnetic sheet has a large elasticity, so that the alloy ribbon cannot be divided finely if the applied external force is small. On the other hand, if the applied external force is large enough to finely divide the alloy ribbon, unevenness remains on the surface of the resin film or the alloy ribbon. In that case, the magnetic sheet has a gradually changing AC relative magnetic permeability μr over time due to the unevenness of the alloy ribbon being deformed by the elasticity of the resin film or the interval between the divided ribbons being changed. Therefore, the AC relative magnetic permeability μr may differ between the time of mass production and after the magnetic sheet is assembled into the electronic device. As a result, a problem occurs in which the characteristics of the electronic device cannot be fully obtained.

[0007] Therefore, the problem that the invention aims to solve is to provide a method and an apparatus for manufacturing an alloy ribbon laminate that can achieve at least one of the following: reducing the magnitude of the external force used to divide an alloy ribbon into multiple pieces, improving the planar condition of the divided alloy ribbons, and suppressing changes in magnetic properties over time. The alloy ribbon laminate can be applied to, for example, a magnetic sheet. However, the alloy ribbon laminate is not limited to a magnetic sheet, and can be applied to other applications as a laminate of alloy ribbons having cracks formed therein. [Means for solving the problem]

[0008] Specific means for solving the above problems include the following aspects. <1> A method for producing an alloy ribbon laminate, comprising: a step of directly applying an external force to an alloy ribbon of a first laminate member having an adhesive layer and an alloy ribbon, thereby forming a crack in the alloy ribbon, to obtain a first laminate having the adhesive layer and the alloy ribbon with the crack formed therein; a step of directly applying an external force to an alloy ribbon of a second laminate member having an adhesive layer and an alloy ribbon, thereby forming a crack in the alloy ribbon, to obtain at least one second laminate having the adhesive layer and the alloy ribbon with the crack formed therein; and a step of stacking the at least one second laminate on the first laminate, to obtain an alloy ribbon laminate in which the adhesive layer and the alloy ribbon with the crack formed therein are alternately stacked. <2> The step of obtaining the second laminate includes a step of adhering an alloy ribbon to the adhesive layer of a crack tape having an adhesive layer and a release film peelable from the adhesive layer to obtain a second laminate member having the release film, the adhesive layer, and the alloy ribbon; a step of forming a crack in the alloy ribbon by directly applying an external force to the alloy ribbon of the second laminate member; and a step of peeling off the release film to obtain a second laminate having the adhesive layer and the alloy ribbon in which the crack is formed. <1> A method for producing the alloy ribbon laminate according to claim 1. <3> The step of obtaining the first laminate includes a step of adhering an alloy ribbon to the adhesive layer of a crack tape having an adhesive layer and a release film peelable from the adhesive layer to obtain a first laminate member having the release film, the adhesive layer, and the alloy ribbon; a step of forming a crack in the alloy ribbon by directly applying an external force to the alloy ribbon of the first laminate member; and a step of peeling off the release film to obtain a first laminate having the adhesive layer and the alloy ribbon in which the crack is formed. <1> or <2> A method for producing the alloy ribbon laminate according to claim 1. <4> The release film is a resin release film. <2> or <3> A method for producing the alloy ribbon laminate according to claim 1. <5> The adhesive layer is a substrate film coated with an adhesive on both sides. <1> ~ <4> 13. A method for producing the alloy ribbon laminate according to claim 12. <6> The method includes a step of laminating the first laminate onto a protective layer having an adhesive layer and a protective film. <1> ~ <5> 13. A method for producing the alloy ribbon laminate according to claim 12. <7> The step of obtaining the first laminate includes a step of adhering an alloy ribbon to the adhesive layer of a protective layer having an adhesive layer and a protective film to obtain a first laminate member having the protective film, the adhesive layer, and the alloy ribbon, and a step of directly applying an external force to the alloy ribbon of the first laminate member to form a crack in the alloy ribbon, thereby obtaining a first laminate having, in this order, the protective film, the adhesive layer, and the alloy ribbon in which the crack is formed. <1> or <2> A method for producing the alloy ribbon laminate according to claim 1. <8> A step of adhering a protective film to one or both end surfaces in a lamination direction of the alloy ribbon laminate is included. <1> ~ <7> 13. A method for producing the alloy ribbon laminate according to claim 12. <9> The protective film is a resin protective film. <6> ~ <8> 13. A method for producing the alloy ribbon laminate according to claim 12. <10> The step of obtaining the second laminate includes a step of forming the cracks in the alloy ribbon by directly applying an external force to the alloy ribbon in a state in which a release film that can be peeled off from the adhesive layer is placed on a surface of the adhesive layer opposite to the surface on which the alloy ribbon is placed, and a step of peeling off the release film. <1> A method for producing the alloy ribbon laminate according to claim 1. <11> In the step of obtaining the first laminate, the formation of the cracks includes a step of forming the cracks in the alloy ribbon by directly applying an external force to the alloy ribbon in a state in which a protective film or a release film that can be peeled off from the adhesive layer is placed on a surface of the adhesive layer opposite to a surface on which the alloy ribbon is placed. <1> A method for producing the alloy ribbon laminate according to claim 1. <12> In forming the cracks, a convex member is pressed against a plurality of locations on the surface of the alloy ribbon to form a plurality of cracks in the alloy ribbon. <1> ~ <11> 13. A method for producing the alloy ribbon laminate according to claim 12. <13> and forming a network crack connecting the plurality of cracks to each other after pressing the convex member against the alloy ribbon to form the plurality of cracks. <12> A method for producing the alloy ribbon laminate according to claim 1. <14> The alloy ribbon is a nanocrystalline alloy ribbon. <1> ~ <13> 13. A method for producing the alloy ribbon laminate according to claim 12. <15> The nanocrystalline alloy ribbon is a nanocrystalline alloy ribbon obtained by subjecting a nanocrystalline amorphous alloy ribbon to a heat treatment for nanocrystallization while applying tension thereto. <14> A method for producing the alloy ribbon laminate according to claim 1. <16> The nanocrystalline alloy ribbon has the general formula: (Fe 1-a M a ) 100-x-y-z-α-β-γ Cu x S y B z M' α M” β X γ(atomic %), in which in the above general formula, M is Co and / or Ni, M' is at least one element selected from the group consisting of Nb, Mo, Ta, Ti, Zr, Hf, V, Cr, Mn, and W, M" is at least one element selected from the group consisting of Al, platinum group elements, Sc, rare earth elements, Zn, Sn, and Re, X is at least one element selected from the group consisting of C, Ge, P, Ga, Sb, In, Be, and As, and a, x, y, z, α, β, and γ satisfy 0≦a≦0.5, 0.1≦x≦3, 0≦y≦30, 0≦z≦25, 5≦y+z≦30, 0≦α≦20, 0≦β≦20, and 0≦γ≦20, respectively. <14> or <15> A method for producing the alloy ribbon laminate according to claim 1. <17> In the step of obtaining the alloy ribbon laminate, the alloy ribbon laminate obtained by stacking the at least one second laminate on the first laminate is a long alloy ribbon laminate, and the method further includes a step of winding the long alloy ribbon laminate into a roll after the step of obtaining the alloy ribbon laminate. <1> ~ <16> 13. A method for producing the alloy ribbon laminate according to claim 12. <18> The long alloy ribbon laminate wound in a roll shape is unwound and cut out. <17> A method for producing the alloy ribbon laminate according to claim 1. <19> The alloy ribbon laminate obtained by stacking the at least one second laminate on the first laminate in the step of obtaining the alloy ribbon laminate is a long alloy ribbon laminate, and the method further includes a step of processing the long alloy ribbon laminate after the step of obtaining the alloy ribbon laminate. <1> ~ <16> 13. A method for producing the alloy ribbon laminate according to claim 12. <20> a plurality of mechanisms A that adhere an alloy ribbon to an adhesive layer of a tape for cracking, the adhesive layer having an adhesive layer and a release film that can be peeled off from the adhesive layer; a plurality of mechanisms B that apply an external force directly to the alloy ribbon adhered to the tape for cracking to form a crack in the alloy ribbon; a plurality of mechanisms C that peel off the release film and form a laminate having the adhesive layer and the alloy ribbon with the crack formed therein; and a mechanism D that stacks a plurality of laminates formed by the plurality of mechanisms A, the plurality of mechanisms B, and the plurality of mechanisms C, each having the adhesive layer and the alloy ribbon with the crack formed therein, to form an alloy ribbon laminate. <21> A mechanism for processing the alloy ribbon laminate is provided. <20> An apparatus for producing the alloy ribbon laminate according to claim 1. <22> a mechanism for unwinding the alloy ribbon wound in a roll shape, <20> or <21> An apparatus for producing the alloy ribbon laminate according to claim 1. Effect of the Invention

[0009] According to the present disclosure, there is provided a method for manufacturing an alloy ribbon laminate and an apparatus for manufacturing the alloy ribbon laminate, which can perform at least one of reducing the magnitude of an external force for dividing an alloy ribbon into a plurality of pieces, improving the planar state of the divided alloy ribbon, and suppressing changes over time in magnetic properties. For example, according to the present disclosure, the magnitude of an external force applied to the alloy ribbon to form cracks can be reduced, and the planar state of the alloy ribbon in which cracks are formed can be improved. As a result, when the alloy ribbon laminate is formed by stacking the alloy ribbons in which cracks are formed, an alloy ribbon laminate in which the planar state is improved can be obtained. In addition, changes over time in magnetic properties of the alloy ribbon laminate can be suppressed. In addition, an alloy ribbon laminate applicable to a magnetic sheet can be obtained. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a flowchart showing the first embodiment. [Diagram 2] FIG. 2 is a flow chart showing the second embodiment. [Diagram 3] FIG. 3 is a flowchart showing a modification of the second embodiment. [Figure 4] FIG. 4 is a schematic diagram showing a cross section of the laminate obtained in step (1). [Diagram 5] FIG. 5 is a diagram illustrating the laminate obtained in step (2). [Figure 6] FIG. 6 is a diagram illustrating the laminate obtained in the step (3). [Figure 7] FIG. 7 is a schematic diagram showing the magnetic sheet obtained in step (4). [Figure 8] FIG. 8 is a diagram for explaining the state of cracks and / or fissures (network cracks) in the alloy ribbon connecting the cracks. [Figure 9] FIG. 9 is a schematic diagram showing a cross section of the laminate obtained in step (5). [Figure 10] FIG. 10 is a schematic diagram showing the laminate obtained in step (6). [Figure 11] FIG. 11 is a schematic diagram showing the magnetic sheet obtained in step (7). [Figure 12] FIG. 12 is a diagram showing a schematic diagram of another magnetic sheet obtained in the second embodiment. [Figure 13] FIG. 13 is a diagram showing a manufacturing apparatus used in the first embodiment. [Figure 14] FIG. 14 is a diagram showing a manufacturing apparatus used in the second embodiment. [Figure 15] FIG. 15 is a plan view of the alloy ribbon showing the locations where an external force is applied by the convex members. [Figure 16] FIG. 16 is a cross-sectional photograph showing an example of a magnetic sheet obtained by the manufacturing method of an alloy ribbon laminate according to the present disclosure. [Figure 17] FIG. 17 is a cross-sectional photograph of a magnetic sheet obtained by a conventional manufacturing method. [Figure 18] FIG. 18 is a cross-sectional photograph of a magnetic sheet obtained by a conventional manufacturing method. [Figure 19] FIG. 19 is a diagram showing the change in magnetic permeability when a conventional magnetic sheet is left to stand after production. [Figure 20] FIG. 20 is a schematic diagram of a non-contact charging device. [Figure 21] FIG. 21 is a schematic diagram of an in-line annealing device for obtaining a nanocrystalline alloy ribbon. [Figure 22] FIG. 4 is a plan view showing a state of cracks formed in the alloy ribbon. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, embodiments of the present disclosure will be described in detail. The present disclosure is not limited to the following embodiments, and can be implemented with appropriate modifications within the scope of the object of the present disclosure.

[0012] When describing the embodiments of the present disclosure with reference to the drawings, the description of the same components and reference numerals in the drawings may be omitted. Components indicated by the same reference numerals in the drawings are the same components. The dimensional ratios in the drawings do not necessarily represent the actual dimensional ratios.

[0013] In the present disclosure, a numerical range indicated using "~" indicates a range including the numerical values ​​described before and after "~" as the lower and upper limits, respectively. In the numerical ranges described in stages in the present disclosure, the upper or lower limit described in a certain numerical range may be replaced with the upper or lower limit of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit described in a certain numerical range may be replaced with a value shown in the examples.

[0014] In this disclosure, ordinal numbers (e.g., "first" and "second") are terms used to distinguish components, and do not limit the number of components or the priority of the components.

[0015] In the present disclosure, the term "process" includes not only independent processes, but also processes that cannot be clearly distinguished from other processes as long as the intended purpose of the process is achieved.

[0016] In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments.

[0017] Conventionally, in order to manufacture a magnetic sheet in which a plurality of alloy ribbons made of a soft magnetic material are laminated and cracks are formed in the alloy ribbons, a plurality of alloy ribbons are laminated to form a magnetic sheet, and then an external force is applied to form cracks in the alloy ribbons. Also, a laminated sheet is formed by attaching a protective film or the like to both sides of at least one layer of the alloy ribbon, and then the laminated sheet is subjected to a flake treatment.

[0018] One of the features of the present disclosure is that, before a plurality of alloy ribbons are stacked, an external force is directly applied to each alloy ribbon to form a crack in each alloy ribbon. In the present disclosure, cracks are formed by directly applying an external force to the alloy ribbon, and cracks are formed on each individual alloy ribbon, which makes it possible to eliminate the need for an excessively large external force for forming cracks and suppress excessive deformation of the alloy ribbon. In other words, the magnitude of the external force applied to the alloy ribbon for forming cracks can be reduced, and the planar state of the alloy ribbon in which the cracks are formed can be improved. A plurality of the alloy ribbons obtained as described above are stacked to form an alloy ribbon laminate in which the alloy ribbons having cracks and the adhesive layers are alternately stacked, thereby obtaining an alloy ribbon laminate having desired properties and suppressing deformation. The alloy ribbon laminate according to the present disclosure can be applied as, for example, a magnetic sheet. The alloy ribbon laminate according to the present disclosure can also be formed into a block-shaped laminate or a toroidal-shaped laminate for use. For example, the alloy ribbon laminate according to the present disclosure can be used as an inductive element or the like.

[0019] One embodiment of the present disclosure is a method for producing an alloy ribbon laminate, comprising: (1) a step of directly applying an external force to an alloy ribbon of a first laminate member having an adhesive layer and an alloy ribbon, thereby forming a crack in the alloy ribbon, to obtain a first laminate having the adhesive layer and the alloy ribbon with the crack formed therein; (2) a step of directly applying an external force to an alloy ribbon of a second laminate member having an adhesive layer and an alloy ribbon, thereby forming a crack in the alloy ribbon, to obtain at least one second laminate having the adhesive layer and the alloy ribbon with the crack formed therein; and (3) a step of stacking the at least one second laminate on the first laminate, thereby obtaining an alloy ribbon laminate in which the adhesive layer and the alloy ribbon with the crack formed therein are alternately stacked.

[0020] In the manufacturing method of the alloy ribbon laminate according to an embodiment of the present disclosure, an external force is applied directly to one alloy ribbon to form a crack, and the applied external force is applied directly to the alloy ribbon, and the strength is only enough to crack one alloy ribbon. As a result, the applied external force can be made smaller than in the conventional manufacturing method in which a plurality of alloy ribbons are laminated and then an external force is applied simultaneously to form a crack, or in the conventional manufacturing method in which an external force is applied from above a protective film to form a crack, and the surface state of the divided alloy ribbons can be made into a good flat state with reduced unevenness. Note that the "good flat state" means that the surface of the object is free of unevenness or has few unevenness. When the term "good flat state" is used with respect to the divided alloy ribbon, the "good flat state" means that when each divided alloy ribbon is viewed continuously, it is generally flat, in addition to the above meaning.

[0021] In the present disclosure, the term "laminate member" is used to distinguish from a laminate having an alloy ribbon in which a crack is formed, and refers to a laminate having an alloy ribbon before cracks are formed. As described later, for example, a laminate member can be formed by adhering an alloy ribbon to the adhesive layer of a crack tape having an adhesive layer and a release film that can be peeled off from the adhesive layer. Also, for example, a laminate member can be formed by adhering an alloy ribbon to the adhesive layer of a protective layer having an adhesive layer and a protective film.

[0022] In this disclosure, the term "second laminate" is used to distinguish it from the first laminate and refers to one or more laminates that are laminated to the first laminate.

[0023] In the manufacturing method of the alloy ribbon laminate according to one embodiment of the present disclosure, at least one second laminate is laminated on the first laminate to form a region in which the adhesive layer and the alloy ribbon having the crack are laminated alternately. For example, the alloy ribbon of a certain laminate (e.g., the first laminate) is brought into contact with the adhesive layer of another laminate (e.g., the second laminate) to form a region in which the adhesive layer and the alloy ribbon having the crack are laminated alternately. The layer structure of the alloy ribbon laminate is not limited as long as it has a region in which the adhesive layer and the alloy ribbon having the crack are laminated alternately. The minimum unit of the region in which the adhesive layer and the alloy ribbon having the crack are laminated alternately is "adhesive layer / alloy ribbon having the crack / adhesive layer / alloy ribbon having the crack" formed by laminating two laminates (i.e., the first laminate and the second laminate). The number of the second laminates laminated on the first laminate may be two or more. When the number of the second laminates is two or more, for example, the second laminates may be laminated one by one on the first laminate. The outermost layers located on one side or both sides in the lamination direction of the alloy ribbon laminate may be layers other than the adhesive layer and the metal ribbon on which the crack is formed (e.g., a protective film). As long as an alloy ribbon laminate in which the adhesive layer and the alloy ribbon on which the crack is formed are alternately laminated can be obtained, the first laminate may be laminated on the second laminate.

[0024] In addition, in some embodiments, when cracks are formed, the alloy ribbon is in a state of being adhered to the release film or protective film via the adhesive layer, so that the elastic force of the release film or protective film further suppresses the occurrence of unevenness on the surface of the alloy ribbon. Even if unevenness occurs on the surface of the alloy ribbon, the elastic force of the release film or protective film deforms the unevenness so that it becomes flat. Hereinafter, some embodiments in which a release film or protective film is used when cracks are formed in the alloy ribbon will be described.

[0025] For example, in the step of obtaining the first laminate, the formation of cracks preferably includes a step of forming the cracks in the alloy ribbon by directly applying an external force to the alloy ribbon in a state where a "protective film" or a "release film" that can be peeled off from the adhesive layer is placed on the surface opposite to the surface on which the alloy ribbon is placed of the adhesive layer. By directly applying an external force to the alloy ribbon adhered to the protective film or release film via the adhesive layer, an alloy ribbon with a good surface condition can be obtained. In the above method, the protective film or release film may be placed at least when the external force is directly applied to the alloy ribbon. For example, after preparing a first laminate member having an adhesive layer and an alloy ribbon, and a protective film or release film, respectively, an external force may be applied directly to the alloy ribbon when the adhesive layer of the first laminate member is brought into contact with the protective film or release film. For example, a first laminate member having a protective film or release film, an adhesive layer, and an alloy ribbon may be prepared in advance, and then an external force may be applied directly to the alloy ribbon. After the cracks are formed, the release film may be peeled off as necessary.

[0026] For example, the step of obtaining the first laminate preferably includes the steps of: (1) adhering an alloy ribbon to the adhesive layer of a crack tape having an adhesive layer and a release film peelable from the adhesive layer to obtain a first laminate member having the release film, the adhesive layer, and the alloy ribbon; (2) directly applying an external force to the alloy ribbon of the first laminate member to form a crack in the alloy ribbon; and (3) peeling off the release film to obtain a first laminate having the adhesive layer and the alloy ribbon with the crack formed therein. By directly applying an external force to the alloy ribbon adhered to the release film via the adhesive layer, an alloy ribbon with a good surface condition can be obtained.

[0027] For example, the step of obtaining the first laminate preferably includes the steps of: (1) adhering an alloy ribbon to the adhesive layer of a protective layer having an adhesive layer and a protective film to obtain a first laminate member having the protective film, the adhesive layer, and the alloy ribbon; and (2) directly applying an external force to the alloy ribbon of the first laminate member to form a crack in the alloy ribbon, thereby obtaining a first laminate having, in this order, the protective film, the adhesive layer, and the alloy ribbon with the crack formed therein. By directly applying an external force to the alloy ribbon adhered to the protective film via the adhesive layer, an alloy ribbon with a good surface condition can be obtained.

[0028] For example, the step of obtaining the second laminate preferably includes the steps of (1) forming the cracks in the alloy ribbon by directly applying an external force to the alloy ribbon in a state where a release film that can be peeled off from the adhesive layer is placed on the surface of the adhesive layer opposite to the surface on which the alloy ribbon is placed, and (2) peeling off the release film. By directly applying an external force to the alloy ribbon bonded to the release film via the adhesive layer, an alloy ribbon with a good surface condition can be obtained. In the above method, the release film only needs to be placed at least when the external force is directly applied to the alloy ribbon. For example, after preparing a second laminate member having an adhesive layer and an alloy ribbon, and a release film, respectively, an external force may be applied directly to the alloy ribbon when the adhesive layer of the second laminate member is brought into contact with the release film. For example, an external force may be applied directly to the alloy ribbon after a second laminate member having a release film, an adhesive layer, and an alloy ribbon is previously prepared.

[0029] For example, the step of obtaining the second laminate preferably includes the steps of: (1) adhering an alloy ribbon to the adhesive layer of a crack tape having an adhesive layer and a release film peelable from the adhesive layer, thereby obtaining a second laminate member having the release film, the adhesive layer, and the alloy ribbon; (2) directly applying an external force to the alloy ribbon of the second laminate member to form a crack in the alloy ribbon; and (3) peeling off the release film to obtain a second laminate having the adhesive layer and the alloy ribbon with the crack formed therein. By directly applying an external force to the alloy ribbon adhered to the release film via the adhesive layer, an alloy ribbon with a good surface condition can be obtained.

[0030] As described above, the alloy ribbon laminate according to the present disclosure is produced by stacking alloy ribbons in a good flat state, and therefore the surface of the alloy ribbon laminate also has a good flat state. As a result, factors that cause fluctuations in magnetic properties can be reduced, and an alloy ribbon laminate with magnetic properties that change little over time can be obtained.

[0031] The alloy ribbon laminate according to the present disclosure may be a long alloy ribbon laminate. The alloy ribbon laminate obtained by stacking at least one second laminate on a first laminate in the step of obtaining an alloy ribbon laminate is preferably a long alloy ribbon laminate. The long alloy ribbon laminate can be manufactured, for example, by using a long alloy ribbon. When a long alloy ribbon laminate is obtained in the step of obtaining an alloy ribbon laminate, the manufacturing method of the alloy ribbon laminate according to an embodiment of the present disclosure preferably includes a step of winding the long alloy ribbon laminate in a roll after the step of obtaining the alloy ribbon laminate. Furthermore, the manufacturing method of the alloy ribbon laminate according to an embodiment of the present disclosure preferably includes a step of unwinding and cutting out the long alloy ribbon laminate wound in a roll. Furthermore, when a long alloy ribbon laminate is obtained in the step of obtaining an alloy ribbon laminate, the manufacturing method of the alloy ribbon laminate according to an embodiment of the present disclosure preferably includes a step of processing (preferably cutting out) the long alloy ribbon laminate after the step of obtaining the alloy ribbon laminate. Through the above steps, an alloy ribbon laminate processed into a desired shape can be obtained.

[0032] The present disclosure will be described in further detail below, but the present disclosure is not limited to this embodiment. In the following, the alloy ribbon laminate of the present disclosure will be described by taking a magnetic sheet, which is one embodiment of the alloy ribbon laminate, as an example. This magnetic sheet corresponds to the alloy ribbon laminate of the present disclosure.

[0033] [Magnetic sheet] An example of the magnetic sheet of the present disclosure is a laminate of a plurality of alloy ribbons made of a soft magnetic material, in which cracks are formed in the alloy ribbons. Note that the cracks in the present disclosure refer to magnetic gaps formed in the alloy ribbons, and include, for example, cracks and / or fissures in the alloy ribbons.

[0034] The magnetic sheet preferably has an alloy ribbon in which cracks and / or fissures (hereinafter referred to as network cracks) are formed in the alloy ribbon connecting the cracks. By forming network cracks in the alloy ribbon, for example, the effect described in JP 2018-112830 A can be obtained. That is, when the magnetic sheet is used as a magnetic body for an inductor, the Q value can be further improved. Also, when the magnetic sheet is used as a magnetic body for a magnetic shield, the current path of the alloy ribbon can be divided, and eddy current loss can be further reduced.

[0035] In the magnetic sheet of the present disclosure, a plurality of alloy ribbons are laminated. The alloy ribbons are laminated to each other, for example, via an adhesive layer. The adhesive layer can be formed using a known adhesive, such as an acrylic adhesive, a silicone adhesive, a urethane adhesive, synthetic rubber, or natural rubber. Acrylic adhesives are preferable because they have excellent heat resistance and moisture resistance, and can bond a wide range of materials. The adhesive layer in the present disclosure may have a single-layer structure or a multi-layer structure. For example, the adhesive layer may be an adhesive layer having a single-layer structure including an adhesive. The adhesive layer may be a substrate film coated with an adhesive on both sides (layer structure: adhesive / substrate film / adhesive). When three or more layers of the alloy ribbon are laminated, the adhesive layers between the layers may be the same or different.

[0036] [Protective film] The magnetic sheet may further be laminated with a protective film. The protective film functions to prevent the alloy ribbon from unnecessarily increasing cracks or network cracks, from falling off, or from rusting due to unintended external forces. The protective film also functions to prevent the occurrence of unnecessary deformation, such as the occurrence of surface irregularities, when the magnetic sheet is processed into a predetermined shape. The protective film may be laminated alone or as a protective layer having an adhesive layer and a protective film. When laminated alone, the alloy ribbon and the protective film may be adhered to each other by an adhesive layer of a sheet member (an example of a laminate in the present disclosure, the same applies below) described later. When laminated as a protective layer, the alloy ribbon and the protective film may be adhered to each other by an adhesive layer of the protective layer. The protective film is preferably laminated so as to cover the exposed alloy ribbon. In addition, when forming a protective layer on a magnetic sheet, a method of laminating a sheet member on the protective layer, or a method of adhering an alloy ribbon to the protective layer, directly applying an external force to the alloy ribbon to form a crack in the alloy ribbon, and laminating a sheet member on the alloy ribbon with the crack formed therein can be used. A specific example of the former method is a step of laminating a first laminate on a protective layer having an adhesive layer and a protective film. In the above step, it is preferable to bring the adhesive layer of the protective layer into contact with the adhesive layer of the first laminate.

[0037] The protective film is preferably a resin protective film, and more preferably a resin protective film having elasticity. As described above, for example, the step of obtaining the first laminate may include a step of (1) adhering an alloy ribbon to the adhesive layer of a protective layer having an adhesive layer and a protective film, thereby obtaining a first laminate member having the protective film, the adhesive layer, and the alloy ribbon, and a step of (2) forming a crack in the alloy ribbon by directly applying an external force to the alloy ribbon of the first laminate member, thereby obtaining a first laminate having the protective film, the adhesive layer, and the alloy ribbon with the crack formed therein, in this order. If the protective film is made of resin, the elastic force of the protective film further suppresses the occurrence of unevenness itself on the surface of the alloy ribbon. In addition, even if unevenness occurs on the surface of the alloy ribbon, the elastic force of the protective film deforms the unevenness so that it becomes flat. As a result, an alloy ribbon in a good flat state can be obtained, and a magnetic sheet with small change in magnetic properties over time can be obtained. For example, a resin with a lower limit of tensile modulus of elasticity of 0.1 GPa can be used as the resin for the protective film. If the tensile modulus of elasticity is 0.1 GPa or more, the above-mentioned effects are likely to be sufficiently obtained. The lower limit of the tensile modulus of elasticity is preferably 0.5 GPa, more preferably 1.0 GPa. The upper limit of the tensile modulus of elasticity is preferably 10 GPa. If the tensile modulus of elasticity exceeds 10 GPa, deformation of the alloy ribbon may be suppressed when cracks are formed. The upper limit of the tensile modulus of elasticity is preferably 7 GPa, more preferably 5 GPa.

[0038] The protective film preferably has a thickness of 1 μm to 100 μm. If the protective film is thicker, it becomes difficult to deform, which may hinder the arrangement of the magnetic sheet along a curved or bent surface. If the thickness is less than 1 μm, the protective film itself becomes more easily deformed, making handling difficult and the function of supporting the alloy ribbon may not be sufficiently obtained. Furthermore, the strength of the film is weakened, which may result in an insufficient protective function. Magnetic y sheets used in mobile devices such as smartphones and mobile phones are required to be thin. Therefore, the upper limit of the thickness of the protective film of a magnetic sheet for mobile devices is preferably 100 μm or less, and more preferably 20 μm.

[0039] In addition, the protective layer may be a release film that can be peeled off from the adhesive layer, in which case the protective layer functions as a protective layer until the protective film is peeled off. After the protective film is peeled off, the magnetic sheet is attached to the object to be shielded, such as an electronic device, by the adhesive layer. In this case, for the purpose of improving the processability of the magnetic sheet, the protective film may have a thickness of more than 20 μm.

[0040] The protective film can be laminated on one or both end faces in the lamination direction of the magnetic sheet. At least one of the protective films arranged on both end faces in the lamination direction of the magnetic sheet can be made peelable from the adhesive layer. For example, the protective film can be laminated on one or both end faces in the lamination direction of the magnetic sheet by a process of adhering the protective film to one or both end faces in the lamination direction of the magnetic sheet. Moreover, after a plurality of sheet members are laminated to obtain an alloy ribbon laminate, the protective film can be adhered to one or both end faces in the lamination direction of the alloy ribbon laminate.

[0041] Examples of resins that can be used for the protective film include polyethylene terephthalate (PET), polyimide, polyetherimide, polyethylene naphthalate, polypropylene, polyethylene, polystyrene, polycarbonate, polysulfone, polyether ketone, polyvinyl chloride, polyvinyl alcohol, fluororesin, acrylic resin, cellulose, etc. From the viewpoints of heat resistance and dielectric loss, polyamide and polyimide are particularly preferred.

[0042] The adhesive layer of the protective layer may be a known adhesive, for example a pressure-sensitive adhesive. Examples of the pressure-sensitive adhesive include acrylic, silicone, urethane, synthetic rubber, natural rubber, and other pressure-sensitive adhesives. The adhesive layer may be a substrate film coated with an adhesive on both sides (layer structure: adhesive / substrate film / adhesive).

[0043] [Alloy ribbon] As the alloy ribbon, for example, an alloy ribbon having a thickness of 100 μm or less produced by roll quenching can be used. The thickness of the alloy ribbon is preferably 50 μm or less, more preferably 30 μm or less, and particularly preferably 25 μm or less. If the thickness of the alloy ribbon is too thin, it becomes difficult to handle, so the thickness of the alloy ribbon is preferably 5 μm or more, and more preferably 10 μm or more. For example, the alloy ribbon may have an Fe-based or Co-based alloy composition, and may be a nanocrystalline alloy or an amorphous alloy. As the alloy ribbon, it is preferable to use an alloy ribbon made of a nanocrystalline alloy (hereinafter, sometimes referred to as a "nanocrystalline alloy ribbon"). The nanocrystalline alloy ribbon is mechanically more fragile than an amorphous alloy ribbon, and when an external force is directly applied to the alloy ribbon to form a crack, the crack is formed with a small external force. Therefore, since the crack can be formed without forming substantially unevenness on the surface of the alloy ribbon, the alloy ribbon can be made in a good flat state, and the change over time in the shape of the alloy ribbon after being made into a magnetic sheet is small, and the change over time in the magnetic properties can be suppressed. As described above, in one embodiment, the cracks are formed by directly applying an external force to the alloy ribbon in a state where a protective film or a release film that can be peeled off from the adhesive layer is placed on the surface opposite to the surface on which the alloy ribbon is placed of the adhesive layer. According to the above method, the cracks can be easily formed in the nanocrystalline alloy ribbon, so that the deformation of the release film or protective film due to the external force can be suppressed. Therefore, the alloy ribbon can be made in a good flat state, and a magnetic sheet with small change in magnetic properties over time can be obtained.

[0044] The nanocrystalline alloy ribbon is produced by a production method including, for example, a step of quenching a molten alloy to obtain an amorphous alloy ribbon capable of nanocrystallization, and a step of heat-treating the amorphous alloy ribbon at a crystallization onset temperature or higher to form fine crystal grains. The heat treatment temperature varies depending on the alloy composition, but is generally 450°C or higher. The fine crystal grains are, for example, Fe with a body-centered cubic lattice structure in which Si and other elements are dissolved. The fine crystal grains can be analyzed using X-ray diffraction and transmission electron microscopy. In the nanocrystalline alloy, at least 50% by volume of the nanocrystalline alloy is made up of fine crystal grains with an average grain size of 100 nm or less measured at the maximum dimension. The portion of the nanocrystalline alloy other than the fine crystal grains is mainly amorphous. The proportion of the fine crystal grains may be substantially 100% by volume.

[0045] As the nanocrystalline alloy ribbon, a nanocrystalline alloy ribbon obtained by subjecting an amorphous alloy ribbon capable of being nanocrystalline to a heat treatment for nanocrystalline formation while applying tension thereto can be used.

[0046] An example of the alloy composition of the amorphous alloy ribbon capable of nanocrystallization is a composition represented by the following general formula. For example, by heat treating an amorphous alloy ribbon having a composition represented by the following general formula, a nanocrystalline alloy ribbon having a composition represented by the following general formula can be obtained. The nanocrystalline alloy ribbon preferably has a composition represented by the following general formula.

[0047] General formula: (Fe 1-a M a ) 100-x-y-z-α-β-γ Cu x S y B z M' α M” β X γ (atom%)

[0048] In the above general formula, M is Co and / or Ni, M' is at least one element selected from the group consisting of Nb, Mo, Ta, Ti, Zr, Hf, V, Cr, Mn, and W, M" is at least one element selected from the group consisting of Al, platinum group elements, Sc, rare earth elements, Zn, Sn, and Re, X is at least one element selected from the group consisting of C, Ge, P, Ga, Sb, In, Be, and As, and a, x, y, z, α, β, and γ satisfy 0≦a≦0.5, 0.1≦x≦3, 0≦y≦30, 0≦z≦25, 5≦y+z≦30, 0≦α≦20, 0≦β≦20, and 0≦γ≦20, respectively. Preferably, in the above general formula, a, x, y, z, α, β, and γ are 0≦a≦0.1, 0.7≦x≦1.3, 12≦y≦17, 5≦z≦10, 1.5≦α≦5, 0≦β≦1, and 0≦γ≦1, respectively.

[0049] Next, an embodiment of the heat treatment will be described in the case where a nanocrystalline alloy ribbon obtained by subjecting an amorphous alloy ribbon capable of nanocrystallization to a heat treatment for nanocrystallization while applying tension thereto is used as the alloy ribbon.

[0050] First, a process for preparing the amorphous alloy ribbon capable of being nanocrystallized according to this embodiment will be described. The amorphous alloy ribbon capable of nanocrystallization is, for example, an alloy ribbon in an amorphous state in which nanocrystals are generated by heat treatment, and can be manufactured by quenching and solidifying a molten metal mixed with an alloy composition that becomes a nanocrystalline alloy. A method called a single roll method or a twin roll method can be used to quench and solidify the molten metal. These are methods using roll cooling. Well-known methods can be applied to this method using roll cooling. In this method using roll cooling, the molten metal is continuously quenched to obtain a long amorphous alloy ribbon. The one quenched and solidified in a ribbon shape does not have nanocrystals and is in an amorphous state, and is then subjected to heat treatment to generate nanocrystals (nanocrystallization) to become a nanocrystalline alloy ribbon. In addition, this long amorphous alloy ribbon is often wound around a winding shaft and transported as a roll-shaped wound body. In addition, fine crystals may be present in the amorphous alloy ribbon capable of nanocrystallization. In that case, the fine crystals become nanocrystals by heat treatment.

[0051] Next, a process of obtaining a nanocrystalline alloy ribbon by performing a heat treatment for nanocrystallization while applying tension to the amorphous alloy ribbon of this embodiment will be described. By applying tension to an amorphous alloy ribbon capable of nanocrystallization and performing a heat treatment for nanocrystallization, it is possible to adjust the AC relative magnetic permeability μr of the nanocrystalline alloy ribbon. It is preferable to obtain a nanocrystalline alloy ribbon having an AC relative magnetic permeability μr of 100 to 2000 by this process. The nanocrystalline alloy is an alloy having a microcrystalline structure with a grain size of 100 nm or less. In this embodiment, for example, an amorphous alloy ribbon is continuously run under tension, and a part of the amorphous alloy ribbon is nano-crystallized. Nano-crystallization is performed by applying heat equal to or higher than the crystallization start temperature, and for example, a means of passing through a heat treatment furnace or contacting with a heat transfer medium can be adopted. In a specific embodiment, for example, the amorphous alloy ribbon under tension is brought into contact with the heat transfer medium, and the amorphous alloy ribbon is continuously run while maintaining contact with the heat transfer medium. Then, the amorphous alloy ribbon is heat-treated by passing through the heat transfer medium, and becomes a nano-crystalline alloy ribbon. At this time, the direction of the tension applied to the amorphous alloy ribbon is the same as the running direction of the amorphous alloy ribbon just before contacting the heat transfer medium, the running direction of the amorphous alloy ribbon when in contact with the heat transfer medium, and the running direction of the nanocrystalline alloy ribbon just after leaving the heat transfer medium, and all of them are linear. Thus, when the amorphous alloy ribbon is processed by running it, it is a long amorphous alloy ribbon, and the longitudinal direction of the amorphous alloy ribbon and the direction of the applied tension are the same. However, the amorphous alloy ribbon may meander while passing through transport rollers, etc., on the upstream side in the running direction of the amorphous alloy ribbon "just before contacting the heat transfer medium". Similarly, the nanocrystalline alloy ribbon obtained from the amorphous alloy ribbon may meander while passing through transport rollers, etc., on the downstream side in the running direction of the amorphous alloy ribbon "just after leaving the heat transfer medium". The tension is preferably from 1.0N to 50.0N, more preferably from 2.0N to 40.0N, and particularly preferably from 3.0N to 35.0N. If the tension is 1.0 N or more, the magnetic permeability can be sufficiently reduced. When the tension is 50.0 N or less, breakage of the amorphous alloy ribbon or the nanocrystalline alloy ribbon can be further suppressed.

[0052] In the heat treatment for nanocrystallization in this embodiment, the amorphous alloy ribbon is heated to a temperature equal to or higher than the crystallization temperature Tc1 (for example, 430° C. or higher), which advances nanocrystallization in the structure of the alloy ribbon. The ultimate temperature is preferably 430°C to 600°C. When the attained temperature is 600°C or less (particularly when the B content is 10 atomic % or more and 20 atomic % or less), for example, the frequency of precipitation of Fe-B compounds that may deteriorate the soft magnetic properties (Hc, Bs, etc.) of the nanocrystalline alloy ribbon can be further reduced. It is also preferable that the set ultimate temperature and the temperature of the heat transfer medium are set to the same temperature.

[0053] In addition, when a heat transfer medium is used for the heat treatment of nanocrystallization, examples of the heat transfer medium include a plate and a twin roll, but a plate-shaped medium having many surfaces in contact with the amorphous alloy ribbon is preferable. The plate-shaped contact surface is preferably flat, but may be slightly curved. In addition, suction holes may be provided on the contact surface of the heat transfer medium with the alloy ribbon, and the suction holes may be used to enable decompression and suction. This allows the alloy ribbon to be sucked and adsorbed to the surface of the heat transfer medium having the suction holes, improving the contact of the alloy ribbon with the heat transfer medium and improving the efficiency of the heat treatment.

[0054] Examples of the material for the heat transfer medium include copper, copper alloys (bronze, brass, etc.), aluminum, iron, iron alloys (stainless steel, etc.), etc. Among these, copper, copper alloys, and aluminum are preferred because they have a high thermoelectric coefficient (heat transfer coefficient). The heat transfer medium may be subjected to plating treatment such as Ni plating or Ag plating. In addition, a means for heating the heat transfer medium may be separately provided, and the heated heat transfer medium may be brought into contact with the amorphous alloy ribbon to heat the amorphous alloy ribbon for heat treatment. In addition, the heat transfer medium may be surrounded by any member. In this embodiment, after the temperature is increased to the ultimate temperature, the temperature of the nanocrystalline alloy ribbon may be maintained for a certain period of time on the heat transfer medium. In this embodiment, the obtained nanocrystalline alloy ribbon is preferably cooled (preferably to room temperature). Furthermore, this embodiment may include winding the obtained nanocrystalline alloy ribbon (preferably the nanocrystalline alloy ribbon after the above-mentioned cooling) to obtain a wound body of the nanocrystalline alloy ribbon.

[0055] The thickness of the amorphous alloy ribbon capable of nanocrystallization in this embodiment is preferably in the range of 10 μm to 50 μm. If it is less than 10 μm, the mechanical strength of the alloy ribbon itself is low, making it difficult to stably cast a long alloy ribbon. If it exceeds 50 μm, a part of the alloy is likely to crystallize, and the characteristics may deteriorate. The thickness of the amorphous alloy ribbon is more preferably 11 μm to 30 μm, and further preferably 12 μm to 27 μm. The width of the amorphous alloy ribbon is not particularly limited, but is preferably 5 mm to 300 mm. When the width of the amorphous alloy ribbon is 5 mm or more, the manufacturing suitability of the amorphous alloy ribbon is excellent. When the width of the amorphous alloy ribbon is 300 mm or less, the uniformity of nanocrystallization is further improved in the process of obtaining a nanocrystalline alloy ribbon. The width of the amorphous alloy ribbon is preferably 200 mm or less.

[0056] In this embodiment, the amorphous alloy ribbon can be unwound from an amorphous alloy ribbon formed in a roll-shaped wound body, run while applying tension to the amorphous alloy ribbon, bring the running amorphous alloy ribbon into contact with a heat transfer medium to heat it, nanocrystallize the amorphous alloy ribbon by heat treatment through the heating, obtain a nanocrystalline alloy ribbon, and wind the nanocrystalline alloy ribbon around a roll-shaped wound body. A continuous line can be provided to produce the nanocrystalline alloy ribbon.

[0057] An embodiment of a method for producing a nanocrystalline alloy ribbon by providing a continuous line will be described with reference to Fig. 21. Shown in Fig. 21 is an in-line annealing device 150, which is an apparatus for performing an in-line annealing process in which a long amorphous alloy ribbon is subjected to continuous heat treatment processes including a temperature increase process and a temperature decrease (cooling) process from an unwinding roll to a winding roll to obtain a nanocrystalline alloy ribbon.

[0058] The in-line annealing apparatus 150 includes an unwinding roller 112 (unwinding device) that unwinds the alloy ribbon 110 from a roll 111 of an amorphous alloy ribbon, a heating plate (heat transfer medium) 122 that heats the alloy ribbon 110 unwound from the unwinding roller 112, a cooling plate (heat transfer medium) 132 that cools the alloy ribbon 110 heated by the heating plate 122, and a winding roller 114 (winding device) that winds up the alloy ribbon 110 cooled by the cooling plate 132. In Fig. 21, an arrow R indicates the running direction of the alloy ribbon 110.

[0059] A wound body 111 of an amorphous alloy ribbon is set on the unwinding roller 112 . The unwinding roller 112 rotates about its axis in the direction of the arrow U, whereby the alloy ribbon 110 is unwound from the wound body 111 of the amorphous alloy ribbon. In this example, the unwind roller 112 itself may include a rotation mechanism (eg, a motor), or the unwind roller 112 itself may not include a rotation mechanism. Even if the unwinding roller 112 itself does not have a rotation mechanism, the alloy ribbon 110 is unwound from the amorphous alloy ribbon roll 111 set on the unwinding roller 112 in conjunction with the winding operation of the alloy ribbon 110 by the winding roller 114 described below.

[0060] As shown in the enlarged circled portion in Fig. 21, the heating plate 122 includes a first flat surface 122S on which the alloy ribbon 110 unwound from the unwinding roller 112 runs while being in contact with the first flat surface 122S. The heating plate 122 heats the alloy ribbon 110 running on the first flat surface 122S while being in contact with the first flat surface 122S via the first flat surface 122S. As a result, the running alloy ribbon 110 is stably and rapidly heated and nano-crystallized. The heating plate 122 is connected to a heat source (not shown) and is heated to a desired temperature by heat supplied from the heat source. Instead of being connected to a heat source, or in addition to being connected to a heat source, the heating plate 122 may include a heat source inside the heating plate 122 itself. Examples of the material for the heating plate 122 include stainless steel, Cu, a Cu alloy, and an Al alloy.

[0061] The heating plate 122 is housed in the heating chamber 120 . The heating chamber 120 may include a heat source separate from the heat source for the heating plate 122 to control the temperature of the heating chamber. The heating chamber 120 has openings (not shown) through which the alloy ribbon enters or exits, on both the upstream side and downstream side of the running direction (arrow R) of the alloy ribbon 110. The alloy ribbon 110 enters the heating chamber 120 through an entrance opening, which is an upstream opening, and exits the heating chamber 120 through an exit opening, which is a downstream opening.

[0062] 21, the cooling plate 132 includes a second flat surface 132S on which the alloy ribbon 110 runs while being in contact with the second flat surface 132S. The cooling plate 132 reduces the temperature of the alloy ribbon 110 running on the second flat surface 132S while being in contact with the second flat surface 132S via the second flat surface 132S. The cooling plate 132 may have a cooling mechanism (for example, a water-cooling mechanism), or may not have a particular cooling mechanism. The cooling plate 132 may be made of, for example, stainless steel, Cu, a Cu alloy, or an Al alloy. The cooling plate 132 is housed in the cooling chamber 130 . The cooling chamber 130 may have a cooling mechanism (for example, a water-cooling mechanism), but may not have a particular cooling mechanism. That is, the cooling mode by the cooling chamber 130 may be water-cooling or air-cooling. The cooling chamber 130 has openings (not shown) through which the alloy ribbon enters or exits, on both the upstream side and downstream side of the running direction (arrow R) of the alloy ribbon 110. The alloy ribbon 110 enters the cooling chamber 130 through an entrance port which is an opening on the upstream side, and exits the cooling chamber 130 through an exit port which is an opening on the downstream side.

[0063] The winding roller 114 is equipped with a rotation mechanism (for example, a motor) that rotates about its axis in the direction of the arrow W. By the rotation of the winding roller 114, the alloy ribbon 110 is wound at a desired speed.

[0064] The in-line annealing device 150 includes a guide roller 41, a dancer roller 60 (one of the tensile stress adjusting devices), a guide roller 42, and a pair of guide rollers 43A and 43B, which are arranged along the running path of the alloy ribbon 110 between the unwinding roller 112 and the heating chamber 120. The tensile stress is also adjusted by controlling the operation of the unwinding roller 112 and the winding roller 114. The dancer roller 60 is provided so as to be movable in the vertical direction (the direction of the double-sided arrow in FIG. 21). By adjusting the vertical position of the dancer roller 60, the tensile stress of the alloy ribbon 110 can be adjusted. This allows the heat treatment for nanocrystallization to be performed while tension is being applied to the amorphous alloy ribbon.

[0065] The alloy ribbon 110 unwound from the unwinding roller 112 is guided into the heating chamber 120 via these guide rollers and dancer rollers. The in-line annealing apparatus 150 includes a pair of guide rollers 44A and 44B and a pair of guide rollers 45A and 45B between the heating chamber 120 and the cooling chamber . The alloy ribbon 110 exiting the heating chamber 120 is guided into the cooling chamber 130 via these guide rollers.

[0066] The in-line annealing apparatus 150 is provided, between the cooling chamber 130 and the roller 114, with a pair of guide rollers 46A and 46B, a guide roller 47, a dancer roller 62, a guide roller 48, a guide roller 49, and a guide roller 50 along the running path of the alloy ribbon 110. The dancer roller 62 is provided so as to be movable in the vertical direction (the direction of the double-sided arrow in FIG. 21). By adjusting the vertical position of the dancer roller 62, the tensile stress of the alloy ribbon 110 can be adjusted. The alloy ribbon 110 exiting the cooling chamber 130 is guided to the take-up roller 114 via these guide rollers and dancer rollers.

[0067] In the in-line annealing apparatus 150, guide rollers (43A, 43B, 44A, and 44B) arranged on the upstream and downstream sides of the heating chamber 120 have the function of adjusting the position of the alloy ribbon 110 so as to bring the alloy ribbon 110 into full contact with the first plane 122S of the heating plate 122. In the in-line annealing apparatus 150, guide rollers (45A, 45B, 46A, and 46B) arranged on the upstream and downstream sides of the cooling chamber 130 have the function of adjusting the position of the alloy ribbon 110 so as to bring the alloy ribbon 110 into full contact with the second plane 132S of the cooling plate 132.

[0068] By using this in-line annealing apparatus 150, nanocrystalline alloy ribbons can be produced, and the above-mentioned alloy ribbon laminate can be produced by using the nanocrystalline alloy ribbons.

[0069] [Crack tape] In one embodiment, a tape for cracking is adhered to the alloy ribbon when cracks are formed in the alloy ribbon. The tape for cracking has an adhesive layer and a release film that can be peeled off from the adhesive layer. The tape for cracking is attached to one side of the alloy ribbon and supports the alloy ribbon when the alloy ribbon is cracked. Thereafter, the release film is peeled off to expose the adhesive layer, resulting in a sheet member (one example of a laminate in the present disclosure) having the adhesive layer and the alloy ribbon on which a crack is formed. The sheet member can be bonded to other alloy ribbons or the like by the adhesive layer. The adhesive layer of the tape for cracking remains on the magnetic sheet. Since the release film may be peeled off from the adhesive layer during manufacturing, it may not remain on the magnetic sheet.

[0070] [Release film] The release film is preferably a resin release film, and more preferably a resin release film having elasticity. The manufacturing method of the alloy ribbon laminate according to one embodiment of the present disclosure includes a step of adhering an alloy ribbon to a crack tape having an adhesive layer and a release film that can be peeled off from the adhesive layer, and a step of directly applying an external force to the alloy ribbon to form a crack. In this case, if the release film is made of resin, the elastic force of the release film suppresses the occurrence of unevenness on the surface of the alloy ribbon. Even if unevenness occurs on the surface of the alloy ribbon, the elastic force of the release film deforms the unevenness so that it becomes flat. This makes it possible to obtain an alloy ribbon in a good flat state, and a magnetic sheet with small changes in magnetic properties over time can be obtained. For example, a resin having a lower limit of tensile modulus of elasticity of 0.1 GPa can be used as the resin for the release film. If the tensile modulus is 0.1 GPa or more, the above-mentioned effects are likely to be sufficiently obtained. The lower limit of the tensile modulus of elasticity is preferably 0.5 GPa, more preferably 1.0 GPa. The upper limit of the tensile modulus of elasticity is preferably 10 GPa. If it exceeds 10 GPa, deformation of the alloy ribbon may be suppressed when cracks are formed. The upper limit of the tensile modulus of elasticity is preferably 7 GPa, more preferably 5 GPa. The resin for the release film can be the same as the resin for the protective film of the protective layer.

[0071] The release film is preferably a release film having a thickness of 1 μm to 100 μm. If the release film is thicker, it becomes difficult to deform, which may hinder the arrangement of the magnetic sheet along a curved or bent surface. If the thickness is less than 1 μm, the release film itself becomes more easily deformed, making it difficult to handle, and the function of supporting the alloy ribbon may not be fully obtained.

[0072] The adhesive layer may be the same as that of the protective layer.

[0073] [crack] The cracks can be formed, for example, by pressing a convex member against the surface of the alloy ribbon. The shape of the convex member may be, for example, rod-like or pyramidal. The tip of the end of the convex member may be flat, pyramidal, inverted pyramidal with a depression in the center, or cylindrical. In forming the cracks, it is preferable to press a convex member against a plurality of positions on the surface of the alloy ribbon to form a plurality of cracks in the alloy ribbon. For example, in forming the cracks, a press member on which a plurality of convex members are regularly arranged can be used. For example, the cracks can be formed using a roll (hereinafter, referred to as a cracking roll) on whose circumferential surface a plurality of convex members are arranged. For example, the cracks can be formed continuously by pressing a long alloy ribbon against a cracking roll or passing the long alloy ribbon between cracking rolls. Also, the cracks can be formed using a plurality of cracking rolls.

[0074] 15 is a plan view of the alloy ribbon showing a location where an external force is applied by a convex member. The shape of the pattern in the alloy ribbon corresponds to the tip shape of the convex member at the location where the external force is applied. FIG. 15(a) conceptually shows the locations where an external force is applied when a convex member having a circular cross-sectional shape at the end is used. FIG. 15(b) conceptually shows the locations where an external force is applied when a convex member having an end with a cross-shaped external shape is used. Figure 15(c) conceptually shows the locations where an external force is applied when a convex member with an end profile that is linear in the vertical direction of the figure and a convex member with an end profile that is linear in the horizontal direction are used. In this figure, the locations where an external force is applied are arranged so that they are discontinuous and in a matrix shape. Figure 15(d) conceptually shows the locations where external forces are applied when using a linear convex member whose end profile is inclined by θ° (inclined by 45° in Figure 15(d)) with respect to the vertical direction of the figure, and a linear convex member whose end profile is inclined by -θ° (inclined by -45° in Figure 15(d)). In this figure, the locations where external forces are applied are discontinuous, and the location where one linear external force is applied is disposed so that its extension intersects between both ends of the location where the other external force is applied. Figure 15(e) conceptually shows the locations where an external force is applied when using a linear convex member whose end profile is tilted by θ° (tilted by 45° in Figure 15(e)) with respect to the vertical direction of the figure, and a linear convex member whose end profile is tilted by -θ° (tilted by -45° in Figure 15(e)). In this figure, the locations where an external force is applied are arranged so that they are discontinuous and inclined in a matrix shape. Fig. 15(f) conceptually shows the locations where external force is applied when a convex member with an end profile that is linear in the vertical direction of the figure and a convex member with an end profile that is linear in the horizontal direction are used, and the positional relationship is changed from Fig. 15(c). The arrangement of the convex members is not limited to that shown in the figure and can be set as appropriate. At the locations where these external forces are applied, it is desirable that cracks of exactly the same shape as those at the locations where these external forces are applied are formed, but it is acceptable that other cracks are formed or that cracks of the same shape are not formed (cracks are only formed partially). Also, the cracks may be linear, and a plurality of cracks may be formed so as to be continuously connected.

[0075] When forming the cracks in Figure 15(c), Figure 15(d), Figure 15(e), or Figure 15(f), for example, one convex member can be placed on a cracking roll and the other convex member can be placed on another cracking roll, and both cracking rolls can sequentially apply an external force directly to the alloy ribbon to form a crack.

[0076] In the formation of cracks using a convex member, it is preferable to further form a network crack that connects the plurality of cracks. Specifically, in an embodiment, it is preferable to have a process of pressing a convex member against the alloy ribbon to form a plurality of cracks, and then forming a network crack that connects the plurality of cracks. For example, after applying an external force directly to the alloy ribbon with a convex member to form cracks, a second external force can be applied by bending or winding the alloy ribbon. This allows the cracks to serve as the starting point of brittle fracture and / or crack fracture, and to form cracks and / or fissures (magnetic gaps that connect the cracks) that connect the cracks. In the process of forming a network crack, the network crack may be formed in the process of forming a plurality of cracks without applying the second external force as described above.

[0077] [Manufacturing process] Hereinafter, the method for producing an alloy ribbon laminate according to the present disclosure will be described with reference to specific embodiments. First, a first embodiment will be described. Fig. 1 is a flow chart of the first embodiment. The first embodiment is a method for producing a magnetic sheet described below. The first embodiment is a manufacturing method of a magnetic sheet in which a plurality of alloy ribbons made of a soft magnetic material are laminated and cracks are formed in the alloy ribbons, the manufacturing method of the magnetic sheet including a step of adhering the alloy ribbon to the adhesive layer of a crack tape having an adhesive layer and a release film peelable from the adhesive layer (step (1) in FIG. 1), a step of directly applying an external force to the alloy ribbon to form a crack (step (2) in FIG. 1), a step of peeling the release film from the adhesive layer to form a sheet member having the adhesive layer and the alloy ribbon in which the cracks are formed (step (3) in FIG. 1), and a step of laminating a plurality of the sheet members (step (4) in FIG. 1). The plurality of sheet members used in the step (4) are supplied, for example, by repeating a series of steps including the steps (1), (2), and (3) multiple times.

[0078] In the first embodiment, in the step (1), an alloy ribbon is bonded to a tape for cracking, which has an adhesive layer and a release film that can be peeled off from the adhesive layer. The crack tape may be one in which the adhesive layer and the release film are integrated, or it may be one in which the adhesive layer and the release film are prepared separately and then integrated.

[0079] 4 is a schematic diagram showing a cross section of the laminated member 10a obtained in step (1). In the laminated member 10a, an alloy ribbon 4, an adhesive layer 3, and a release film 1 are laminated.

[0080] In the first embodiment, in the step (2), an external force is directly applied to the alloy ribbon to form a crack. In this manner, in the present disclosure, cracks are formed by applying an external force directly to the alloy ribbon before stacking the alloy ribbons, not after stacking a plurality of alloy ribbons, so that the applied external force is directly applied to the alloy ribbon and has a strength sufficient to crack one layer of the alloy ribbon. As a result, cracks can be formed with a smaller external force than in the conventional manufacturing method in which cracks are simultaneously formed in a plurality of alloy ribbons or in which an external force is applied from above a protective film to form cracks. Therefore, unevenness on the surface of the alloy ribbon in which cracks are formed can be suppressed, and the flat state of the alloy ribbon can be improved. In addition, in step (2), the cracks are formed while the alloy ribbon is adhered to the release film, so that the elastic force of the release film suppresses the occurrence of unevenness on the surface of the alloy ribbon itself, and the flat state of the alloy ribbon can be improved. Even if unevenness occurs on the surface of the alloy ribbon, the elastic force of the release film can deform the unevenness so that it becomes flat. As a result, a magnetic sheet with small changes in magnetic properties over time can be obtained.

[0081] Fig. 5 is a schematic diagram of the laminate 10b obtained in step (2). Fig. 5(2-a) is a plan view seen in the lamination direction, and Fig. 5(2-b) is a cross-sectional view taken along the line AA in Fig. 5(2-a). The same relationship applies to the upper and lower views (*-a) and (*-b) in Fig. 6, Fig. 7, Fig. 10, Fig. 11, and Fig. 12, which will be described later, and further explanations will be omitted. In the laminate 10b, an alloy ribbon 4, an adhesive layer 3, and a release film 1 are laminated. A plurality of linear cracks 9 extending in the vertical direction of the drawing are regularly formed in the alloy ribbon 4. As shown in FIG. 5(2-b), the cracks 9 are breaks and / or fissures formed in the alloy ribbon 4. As described above, the release film is preferably made of an elastic resin. When linear cracks are formed in the alloy ribbon, they are preferably formed parallel to the casting direction of the alloy ribbon (corresponding to the longitudinal direction in the case of continuous casting (rapid solidification) by roll cooling, and the direction along the rotation direction of the rolls) as shown in Fig. 22. The arrow in Fig. 22 indicates the casting direction.

[0082] In the first embodiment, the release film is peeled off in step (3). Although the release film has not been utilized in conventional manufacturing methods, in the present disclosure, the release film is used as an auxiliary member for preventing unevenness from occurring in the alloy ribbon when an external force is directly applied to the alloy ribbon to form cracks in step (2).

[0083] 6 is a schematic diagram showing the laminate 10c (i.e., sheet member) obtained in step (3). In the laminate 10c (i.e., sheet member), an alloy ribbon 4 and an adhesive layer 3 are laminated. The release film has been peeled off.

[0084] In the first embodiment, a plurality of sheet members are laminated in step (4). The magnetic sheet is produced by laminating the alloy ribbons having no or few irregularities on the surface where cracks are formed in step (2) and having a good flat state, as they are. Therefore, it is possible to obtain a magnetic sheet having small irregularities on the surface of the alloy ribbon after the magnetic sheet is formed, having a good flat state, and having little change in magnetic properties over time.

[0085] 7 is a diagram showing a magnetic sheet 20a (alloy ribbon laminate) obtained in step (4). In the magnetic sheet 20a, a plurality of sheet members are laminated. The plurality of sheet members include three second laminates (10c1 to 10c3) and a first laminate 10c4. In the magnetic sheet 20a of this embodiment, as shown in FIG. 7(4-a), the crack 9 formed in the second laminate 10c1, the crack 9-1 formed in the second laminate 10c2, and the crack 9-2 formed in the second laminate 10c3 are formed at different positions in the lamination direction. In this way, in one example of the present disclosure, the cracks are formed by directly applying an external force to each alloy ribbon, and therefore, unlike the conventional manufacturing method in which cracks are simultaneously formed in a plurality of alloy ribbons, the position of the crack can be changed for each layer of the alloy ribbon, so that a magnetic sheet with an even magnetic gap can be obtained. Therefore, when the magnetic sheet is further processed by punching or cutting into a desired shape, the magnetic permeability varies little depending on the processing position, and a magnetic sheet having stable shielding characteristics can be manufactured. The crack 9-4 of the first laminate 10c4 is formed at a position overlapping the crack 9 formed in the second laminate 10c1.

[0086] As another step in the first embodiment, for example, a step of laminating a protective film on the second laminate 10c1 can be adopted. The protective film can suppress the alloy ribbon from unnecessarily increasing cracks and network cracks due to unintended external forces, from falling off, or from rusting. In addition, the protective film functions to prevent the generation of unnecessary surface irregularities when the magnetic sheet is processed into a predetermined shape. The step of laminating the protective film can be carried out in any of steps (1) to (4).

[0087] Fig. 8 is a diagram for explaining the state of cracks and / or fissures (network cracks) in the alloy ribbon that connect the cracks together. Specifically, Fig. 8 is a schematic diagram showing the form of cracks 9 and network cracks 11 formed in the alloy ribbon. When the cracks 9 are discontinuous, a second external force such as bending or winding may be applied to the alloy ribbon 4 to form cracks and / or fissures in the alloy ribbon 4 with the cracks 9 as starting points of brittle fracture, and the cracks and / or fissures (magnetic gaps that connect the cracks 9 together) may form network cracks 11 that connect the cracks 9 together. The network cracks 11 can be formed at any time after the step (2).

[0088] Next, an example of a manufacturing apparatus for a magnetic sheet used in the first embodiment and a manufacturing method for a magnetic sheet using the manufacturing apparatus will be described with reference to FIG. 13. The manufacturing apparatus for a magnetic sheet shown in FIG. 13 includes a plurality of mechanisms A that bond an alloy ribbon to the adhesive layer of a tape for cracking, the adhesive layer having a release film that can be peeled off from the adhesive layer, a plurality of mechanisms B that directly apply an external force to the alloy ribbon bonded to the tape for cracking to form a crack in the alloy ribbon, a plurality of mechanisms C that peel off the release film and form a laminate having the adhesive layer and the alloy ribbon in which the crack is formed, and a mechanism D that stacks a plurality of laminates having the adhesive layer and the alloy ribbon in which the crack is formed, formed by the plurality of mechanisms A, the plurality of mechanisms B, and the plurality of mechanisms C, to form an alloy ribbon laminate. Furthermore, the manufacturing apparatus for a magnetic sheet shown in FIG. 13 includes a mechanism for unwinding an alloy ribbon wound in a roll shape, and a mechanism for processing a magnetic sheet. The specific product names and values ​​shown below are examples for explaining in detail the magnetic sheet manufacturing method and magnetic sheet manufacturing apparatus.

[0089] An embodiment of the step (1) "a step of adhering an alloy ribbon to an adhesive layer of a tape for cracking, the adhesive layer having an adhesive layer and a release film that can be peeled off from the adhesive layer" First, rolls wrapped with tape 2A are placed in four locations. Then, tape 2A is pulled out from the roll. Tape 2A has a three-layer structure consisting of release film 1A (25 μm), adhesive layer (5 μm), and release film 1B (25 μm). Release film 1A and release film 1B are made of the same material (PET) and have a tensile elasticity of 3.9 GPa. The adhesive layer is a base film coated with an acrylic adhesive on both sides. Release films 1A and 1B can be peeled off from the adhesive layer. The release film 1A is peeled off from the tape 2A. The release film 1A is peeled off at approximately the same time as the tape 2A is pulled out from the roll. In this embodiment, the tape consisting of the adhesive layer obtained by peeling off the release film 1A and the release film 1B is used as a crack tape. The alloy ribbon 4 used in the step (1) is a long alloy ribbon. The alloy ribbon 4 is wound around a roll. The roll around which the alloy ribbon 4 is wound is an example of a mechanism for unwinding an alloy ribbon wound in a roll shape. The alloy ribbon 4 is pulled out from the roll and bonded to an adhesive layer of a tape for cracking by a pressure roll, which is an example of mechanism A. The alloy ribbon 4 is an alloy ribbon (FT-3 manufactured by Hitachi Metals, Ltd.) made of a nanocrystalline alloy of Fe-Cu-Nb-Si-B system. In the manufacturing apparatus shown in FIG. 13, the alloy ribbon 4 is continuously flowed until it is cut by a cutter 7 described later.

[0090] An embodiment of the step (2) "step of directly applying an external force to the alloy ribbon to form a crack" A crack is formed by directly applying an external force to the alloy ribbon 4 adhered to the cracking tape by a cracking roll 5, which is an example of mechanism B. A plurality of protruding members are regularly arranged on the circumferential surface of the cracking roll 5. When forming cracks, a compression roll for pressing the alloy ribbon 4 against the cracking roll can be arranged on the release film 1B side so as to prevent the external force from the cracking roll from escaping.

[0091] An embodiment of step (3) "a step of peeling off the release film from the adhesive layer to form a sheet member having the adhesive layer and the alloy ribbon having cracks formed therein" The release film 1B is peeled off from the adhesive layer of the crack tape to expose the adhesive layer. By peeling off the release film 1B, a sheet member having an alloy ribbon on which an adhesive layer and cracks are formed is formed. The release film 1B is peeled off by a roll, which is an example of mechanism C. A network crack can also be formed by utilizing an external force to the alloy ribbon 4 generated when peeling off the release film 1B. The manufacturing apparatus shown in FIG. 13 has four combinations of mechanisms A, B, and C for performing steps (1) to (3). However, the number of the above combinations is not limited to four, and may be five or more or three or less depending on the purpose.

[0092] Step (4) "Step of stacking a plurality of sheet members" The multiple sheet members manufactured through steps (1) to (3) are laminated by a compression roll so that the adhesive layers and the alloy ribbons are alternately arranged to obtain a magnetic sheet. The compression roll is an example of mechanism D. The multiple sheet members are laminated on a protective layer 6A.

[0093] In the first embodiment shown in FIG. 13, a protective layer 6A is adhered to one end surface in the lamination direction of the magnetic sheet, and a protective film 6a is adhered to the other end surface. The protective layer 6A is adhered to the adhesive layer on one end surface in the lamination direction of the magnetic sheet. The protective layer 6A has a two-layer structure consisting of an adhesive layer with a thickness of 5 μm and a protective film with a thickness of 75 μm. The protective film can be peeled off from the adhesive layer. The adhesive layer of the sheet member and the adhesive layer of the protective layer are adhered by a pressure roller. When the protective film is peeled off, the adhesive layer of the protective layer is exposed, making it possible to attach the magnetic sheet to an electronic device or the like. The protective film 6a is adhered to the alloy ribbon on the other end surface of the magnetic sheet via the adhesive layer of another tape 2B. The tape 2B has a three-layer structure consisting of a release film 1C, an adhesive layer (5 μm), and a release film 1D. The release film 1C and the release film 1D can be peeled off from the adhesive layer. The release film 1C is peeled off from the tape 2B, and the exposed adhesive layer and the alloy ribbon are adhered by a pressure roller. Then, the release film 1D is peeled off. Then, the protective film 6a is pressure-bonded to the adhesive layer of the tape 2B. The protective film 6a is a PET protective film with a thickness of 25 μm.

[0094] In the first embodiment, after the protective film 6a is laminated, the magnetic sheet is cut to a required size by a cutter 7 and conveyed to a tray 8. The cutter 7 is an example of a mechanism for processing the magnetic sheet. Instead of the cutter 7, the magnetic sheet can also be processed into a desired shape by a processing device such as a punch die.

[0095] A second embodiment will now be described with reference to the flowchart of FIG. The second embodiment is a method for producing a magnetic sheet, described below. The second embodiment is a manufacturing method for a magnetic sheet in which a plurality of alloy ribbons made of a soft magnetic material are laminated and cracks are formed in the alloy ribbons, the manufacturing method for the magnetic sheet including the steps of: adhering an alloy ribbon to an adhesive layer of a crack tape having an adhesive layer and a release film peelable from the adhesive layer (step (1) in FIG. 2); applying an external force directly to the alloy ribbon to form a crack (step (2) in FIG. 2); peeling the release film from the adhesive layer to form a sheet member having the adhesive layer and the alloy ribbon in which the crack is formed (step (3) in FIG. 2); adhering an alloy ribbon to the adhesive layer of a protective layer having an adhesive layer and a protective film (step (5) in FIG. 2); applying an external force directly to the alloy ribbon adhered to the protective layer to form a crack (step (6) in FIG. 2); and laminating the sheet member on the alloy ribbon adhered to the protective layer (step (7) in FIG. 2).

[0096] The second embodiment includes the same steps (1) to (3) as the first embodiment. Explanation of steps (1) to (3) will be omitted.

[0097] In the second embodiment, in step (5), the alloy ribbon is adhered to the adhesive layer of the protective layer having the adhesive layer and the protective film. The protective layer may be an integrated adhesive layer and protective film, or an adhesive layer and protective film may be prepared separately and then integrated. The step (5) can also be carried out simultaneously with the steps (1) to (3).

[0098] 9 is a diagram showing a schematic cross section of the laminated member 10d obtained in step (5). In the laminated member 10d, the alloy ribbons 4′ and the protective layer 6 composed of the adhesive layer 6b and the protective film 6a are laminated. The protective layer may be one which is sold as an integrated adhesive layer and protective film, or one which is prepared separately and then integrated with the adhesive layer and protective film. The materials of the adhesive layer and the protective film of the protective layer are the same as those described above.

[0099] In the second embodiment, in step (6), an external force is directly applied to the alloy ribbon bonded to the protective layer to form a crack. In this manner, in the present disclosure, the cracks are formed by applying an external force directly to the alloy ribbon before stacking the alloy ribbons, not after stacking the alloy ribbons, so that the applied external force is applied directly to the alloy ribbons and has a strength sufficient to crack one layer of the alloy ribbon. Therefore, the cracks can be formed with a smaller external force than in the conventional manufacturing method in which cracks are simultaneously formed in a plurality of alloy ribbons or in the conventional manufacturing method in which cracks are formed by applying an external force from above a protective film. Since the external force for forming the cracks is small, the unevenness of the surface of the alloy ribbon in which the cracks are formed can be suppressed, and the flat state of the alloy ribbon can be improved. Furthermore, in step (6), the cracks are formed in a state in which the alloy ribbon is bonded to the protective film, so that the elastic force of the protective film suppresses the occurrence of unevenness on the surface of the alloy ribbon itself, and the flat state of the alloy ribbon can be improved. Even if unevenness occurs on the surface of the alloy ribbon, the elastic force of the protective film deforms the unevenness so that it becomes flat. As a result, a magnetic sheet (alloy ribbon laminate) with small changes in magnetic properties over time can be obtained.

[0100] Fig. 10 is a diagram showing a first laminate 10e obtained in step (6). A plurality of linear cracks 9' extending in the vertical direction of the drawing are regularly formed in the alloy ribbon 4'. As shown in Fig. 10(6-b), the cracks 9' are breaks and / or fissures formed in the alloy ribbon 4'.

[0101] The protective film is preferably made of a resin having elasticity. The tensile elastic modulus of the resin, the preferred range of the thickness, and the type of the resin of the protective film are as described above.

[0102] In the second embodiment, in step (7), the sheet member obtained in steps (1) to (3) (i.e., the second laminate 10c3) is laminated on the alloy ribbon bonded to the protective layer. Both the alloy ribbon of the sheet member and the alloy ribbon bonded to the protective layer are alloy ribbons with no or few surface irregularities and good flatness. Since these alloy ribbons are laminated as they are, it is possible to obtain a magnetic sheet in which the surface irregularities of the alloy ribbon after being made into a magnetic sheet are small, the flatness is good, and the change in magnetic properties over time is small.

[0103] FIG. 11 is a schematic diagram showing the magnetic sheet 20b obtained by step (7). As shown in FIG. 11(7-a), in the magnetic sheet 20b, the second laminate 10c3 is laminated on the alloy ribbon 4' bonded to the protective layer 6. In this magnetic sheet 20b, the crack 9 formed in the alloy ribbon 4 of the second laminate 10c3 and the crack 9' formed in the alloy ribbon 4' bonded to the protective layer 6 are formed at different positions when viewed in the lamination direction. In this manner, in the present disclosure, the cracks are formed by directly applying an external force to each alloy ribbon, and therefore, unlike the conventional manufacturing method in which cracks are simultaneously formed in a plurality of alloy ribbons, the position of the crack can be changed for each layer of the alloy ribbon, so that a magnetic sheet in which a magnetic gap is formed evenly can be obtained. Therefore, when this magnetic sheet is further processed by punching or cutting into a desired shape, a magnetic sheet with stable shielding characteristics can be manufactured with little variation in magnetic permeability depending on the processing position. The magnetic sheet may have another protective film or layer laminated on the surface opposite to the protective layer 6 in the lamination direction. In either protective layer, a release film that can be peeled off from the adhesive layer may be used as the protective film.

[0104] In the second embodiment, the network cracks 11 can be formed in the same manner as described with reference to FIG.

[0105] In the second embodiment, a step of laminating another sheet member on the sheet member (step (4) in FIG. 3) can be performed. The step of laminating another sheet member on this sheet member (step (4)) can be a step of laminating a sheet member on the alloy ribbon bonded to the protective layer, and then laminating the still another sheet member on the sheet member. In this case, in the flow chart shown in FIG. 2, step (4) is performed after step (7). Alternatively, a plurality of sheet members may be stacked together, and the stack of sheet members may then be laminated to an alloy ribbon bonded to a protective layer. Figure 3 is a flow chart of this method. In the flow chart of Fig. 3, step (4) of the first embodiment is carried out after step (3) of the second embodiment. The explanation of each step is the same as above. However, the procedure for stacking the alloy ribbons is not limited to this, and can be set each time.

[0106] FIG. 12 is a diagram showing a schematic diagram of another magnetic sheet obtained in the second embodiment. Specifically, the magnetic sheet shown in FIG. 12 is obtained by the process shown in the flow chart of FIG. 3. As shown in FIG. 12(a), the magnetic sheet 20c is obtained by laminating the second laminate 10c1 to the second laminate 10c3 on the alloy ribbon 4' bonded to the protective layer 6. In the magnetic sheet 20c, the cracks 9, 9-1, and 9-2 formed in the second laminate 10c1 to the second laminate 10c3, respectively, and the cracks 9' formed in the alloy ribbon 4' bonded to the protective layer 6 are formed at different positions when viewed in the lamination direction. In this manner, in the present disclosure, the cracks are formed by directly applying an external force to each alloy ribbon, and therefore, unlike the conventional manufacturing method in which cracks are simultaneously formed in a plurality of alloy ribbons, the position of the crack can be changed for each layer of the alloy ribbon, and therefore, a magnetic sheet in which a magnetic gap is formed uniformly can be obtained. Therefore, even if this magnetic sheet is further processed by punching or cutting into the desired shape, there is little variation in magnetic permeability depending on the processing position, and a magnetic sheet with stable shielding characteristics can be produced. In the magnetic sheet 20c, another protective film or protective layer can be laminated on the surface opposite to the protective layer 6 in the lamination direction. In either protective layer, a release film that can be peeled off from the adhesive layer can be used as the protective film.

[0107] Next, an example of a magnetic sheet manufacturing apparatus used in the second embodiment will be described with reference to Fig. 14. The magnetic sheet manufacturing apparatus shown in Fig. 14 has a mechanism similar to that included in the magnetic sheet manufacturing apparatus shown in Fig. 13. Note that, as the second embodiment, a manufacturing method of the steps shown in Fig. 2 will be described. An embodiment of the step (1) "a step of adhering an alloy ribbon to an adhesive layer of a tape for cracking, the adhesive layer having an adhesive layer and a release film that can be peeled off from the adhesive layer" First, rolls wrapped with release film 1E are placed in three locations. In addition, rolls wrapped with tape 2C for bonding an adhesive layer to release film 1E are placed in three locations. Tape 2C has a two-layer structure consisting of an adhesive layer (5 μm) and release film 1F (25 μm). Release film 1E and release film 1F are made of the same material (PET) and have a tensile elasticity of 3.9 GPa. After that, release film 1E and tape 2C are pulled out from the roll and bonded by a pressure roller. The adhesive layer is a base film coated on both sides with an acrylic adhesive. Release film 1F can be peeled off from the adhesive layer. Release film 1E can be peeled off after adhering to the adhesive layer. Thereafter, the release film 1F is peeled off from the adhesive layer. In this embodiment, a tape consisting of the adhesive layer obtained by peeling off the release film 1F and the release film 1E is used as a crack tape. Thereafter, the alloy ribbon 4 is pulled out from the roll and bonded to the exposed adhesive layer by a pressure roller. The alloy ribbon 4 is an alloy ribbon (FT-3 manufactured by Hitachi Metals, Ltd.) made of a nanocrystalline alloy of Fe-Cu-Nb-Si-B system.

[0108] An embodiment of the step (2) "step of directly applying an external force to the alloy ribbon to form a crack" A cracking roll 5 having a plurality of protruding members regularly arranged on its circumferential surface directly applies an external force to the alloy ribbon 4 adhered to the cracking tape, forming a crack. When forming a crack, a compression roll can be arranged on the release film 1E side to prevent the external force from the cracking roll 5 from escaping.

[0109] An embodiment of step (3) "a step of peeling off the release film from the adhesive layer to form a sheet member having the adhesive layer and the alloy ribbon having cracks formed therein" The release film 1E is peeled off from the adhesive layer of the crack tape to expose the adhesive layer. Network cracks can also be formed by utilizing the external force applied to the alloy ribbon 4 that is generated when the release film 1E is peeled off.

[0110] Embodiment of step (5) "step of bonding an alloy ribbon to the adhesive layer of a protective layer having an adhesive layer and a protective film" First, a roll wrapped with protective film 6a1 is placed. A roll wrapped with tape 2C is placed near the roll wrapped with protective film 6a1. Protective film 6a1 and tape 2C are pulled out from the roll, and protective film 6a1 is bonded to the adhesive layer of tape 2C by a pressure roller. As described above, tape 2C has a two-layer structure consisting of an adhesive layer (5 μm) and release film 1F (25 μm). The release film 1F and the protective film 6a1 are made of the same material (PET) and have a tensile elasticity of 3.9 GPa. As the adhesive layer, a base film coated with an acrylic adhesive on both sides is used. The release film 1F can be peeled off from the adhesive layer, and the protective film 6a1 can be peeled off after being adhered to the adhesive layer. Thereafter, the release film 1F is peeled off from the tape 2C. In this embodiment, the tape thus obtained, which is made up of the adhesive layer and the protective film 6a1, is used as a protective layer. Thereafter, the alloy ribbon 4' is pulled out from the roll and adhered to the exposed adhesive layer by a pressure roller. The alloy ribbon 4' may be made of the same material as the alloy ribbon 4, or may be made of a different material.

[0111] An embodiment of step (6) "step of directly applying an external force to the alloy ribbon bonded to the protective layer to form a crack" The cracking roll 5, which has a plurality of protruding members regularly arranged on its circumferential surface, applies an external force directly to the alloy ribbon 4' bonded to the protective layer 6a1 to form cracks. At this time, a compression roll can be arranged on the protective film 6a1 side to prevent the external force from escaping from the cracking roll.

[0112] Step (7) "Laminating a sheet member on the alloy ribbon bonded to the protective layer" The sheet members produced in steps (1) to (3) are laminated on the alloy ribbon 4' bonded to the adhesive layer of the protective layer. In this embodiment, first, one sheet member is adhered to the alloy ribbon 4' adhered to the protective layer, and then, other two sheet members are laminated in sequence.

[0113] In the second embodiment, a protective film 6a2 (thickness 10 μm) is adhered to the end face opposite to the end face to which the protective film 6a1 is adhered in the lamination direction. Tape 2C is adhered to the magnetic sheet obtained in step (7). Then, release film 1F is peeled off from tape 2C to obtain a magnetic sheet having an adhesive layer for a protective film formed on the outermost layer. Then, protective film 6a2 is adhered to this adhesive layer. The protective film 6a1 and the protective film 6a2 may be peelable after being attached to the adhesive layer of the protective layer. In this case, the adhesive layer of the protective layer is exposed by peeling off the protective film, and the protective film 6a1 and the protective film 6a2 can be attached to the electronic device to be magnetically shielded.

[0114] In the second embodiment, after the protective film 6a2 is laminated, the magnetic sheet is cut to a required size by a cutter 7 and conveyed to a tray 8. Instead of using the cutter 7, the magnetic sheet can also be processed into a desired shape by punching.

[0115] 16 is a cross-sectional photograph showing an example of a magnetic sheet obtained by the manufacturing method of an alloy ribbon laminate according to the present disclosure. In the photograph, the white parts are alloy ribbons, and the gray parts between the alloy ribbons are adhesive layers. In addition, an adhesive layer or a protective layer of a sheet member is located on the outer side of the four alloy ribbons in the stacking direction. The presence of cracks or fissures can be observed in the first to third layers from the bottom of the alloy ribbon, indicating the presence of a magnetic gap. Furthermore, there are substantially no irregularities (three-dimensional structures protruding from the surface) on the surfaces of all the alloy ribbons, and the planar condition of the alloy ribbons is good. Furthermore, the planar condition of the magnetic sheet, which is a laminate of four layers, is also good.

[0116] 18 is a cross-sectional photograph of a magnetic sheet obtained by a conventional manufacturing method (a manufacturing method in which a plurality of alloy ribbons are laminated and then an external force is applied to form cracks). In the conventional magnetic sheet, the alloy ribbons are deformed in a wavy manner, and the adhesive layer and the protective layer at the edge are also deformed in a wavy manner. Fig. 17 is a cross-sectional photograph of a magnetic sheet obtained by a conventional manufacturing method. Specifically, the magnetic sheet shown in Fig. 17 is a magnetic sheet obtained by press-molding both sides of the magnetic sheet shown in Fig. 18 with a flat plate-like member to flatten it. In the magnetic sheet in Fig. 17, the alloy ribbons are arranged more flatly than in the magnetic sheet in Fig. 18, but in the lower center part of the photograph, the bottommost alloy ribbon has a double structure, and a three-dimensional structure in which the alloy ribbon protrudes to the surface is formed.

[0117] FIG. 19 is a diagram showing the change in magnetic permeability when a conventional magnetic sheet is left to stand after production. Specifically, FIG. 19 is a diagram showing the results of measuring the AC relative magnetic permeability over the course of 1000 hours in the atmosphere at 70° C., with the time immediately after production of the conventional magnetic sheet being set as 0 hours, and determining the rate of change from the value at 0 hours. In FIG. 19, (a) is a graph showing the real value (real part) μr′ of the AC relative magnetic permeability μr, and (b) is a graph showing the imaginary value (imaginary part) μr″ of the AC relative magnetic permeability μr. In the measurement shown in FIG. 19, a magnetic sheet produced by a conventional production method (a production method in which a plurality of alloy ribbons are laminated and then an external force is applied to form cracks) is used.

[0118] In measuring the AC relative permeability μr, the impedance (Z) and the inductance (L S ) is measured with an impedance analyzer (E4990A manufactured by Keysight Technologies, measuring jig: 16454A) at an OSC level of 0.03 V, a temperature of 25°C and a frequency of 128 kHz, and the AC relative permeability μr is calculated based on the following formula. The evaluation sample is made by stacking 10 to 20 layers of sheets punched into a ring shape with an outer diameter of 20 mm and an inner diameter of 9 mm. μr=2π×Z / (2π×μ0×f×t×n×ln(OD / ID)) Z: Absolute value of impedance f: Frequency (Hz) t: ribbon thickness (m) n: number of layers μ0: Vacuum permeability (4×π×10 -7 H / m) OD: Outer diameter (m) ID: Inner diameter (m)

[0119] As shown in FIG. 19, the magnetic sheet obtained by the conventional manufacturing method has a large change in AC relative permeability μr over time.

[0120] [Contactless charging device] As an example of using the magnetic sheet of the present disclosure, an example of a non-contact charging device is shown. The non-contact charging device has a circuit configuration shown in FIG. 20, for example. The power supply device 200 includes a power supply unit 21 that supplies AC current, a rectifier circuit 22 connected to the power supply unit 21 to rectify the AC current to DC current, a switching circuit 23 that inputs the DC current and converts it into a high-frequency current of a predetermined frequency, a primary coil 201 connected to the switching circuit 23 so that the high-frequency current flows, a resonance capacitor 26 connected in parallel to the primary coil 201 so as to resonate at the same frequency as the switching circuit 23, a control circuit 24 connected to the switching circuit 23, and a control primary coil 25 connected to the control circuit 24. The control circuit 24 controls the operation of the switching circuit 23 based on the induced current obtained from the control primary coil 25.

[0121] The power receiving device 300 includes a secondary coil 301 that receives a magnetic flux generated from the primary coil 201, a rectifier circuit 32 connected to the secondary coil 301, a secondary battery 33 connected to the rectifier circuit 32, a battery control circuit 34 connected to the secondary battery 33 to detect the charge state from the voltage of the secondary battery 33, and a control secondary coil 35 connected to the battery control circuit 34. A resonance capacitor (not shown) may be connected in parallel to the secondary coil 301. The rectified current is stored in the secondary battery 33 and is also used, for example, for electronic circuits and driving members (not shown). The battery control circuit 34 sends a signal to the control secondary coil 35 for optimal charging according to the charge state of the secondary battery 33. For example, when the secondary battery 33 is fully charged, a signal of that information is sent to the control secondary coil 35, and the signal is transmitted to the control circuit 24 of the power supply device 200 via the control primary coil 25 that is electromagnetically coupled to the control secondary coil 35. The control circuit 24 stops the switching circuit 23 based on the signal.

[0122] In a power supply device, the magnetic sheet of the present disclosure is used, for example, between the primary coil 201 and other electronic components of the power supply device, and between the control primary coil 25 and other electronic components of the power supply device. In a power receiving device, the magnetic sheet of the present disclosure is used, for example, between the secondary coil 301 and other electronic components of the power supply device, and between the control secondary coil 35 and other electronic components of the power supply device. EXAMPLES

[0123] The present disclosure will be described in detail below with reference to examples, but the present disclosure is not limited to the following examples.

[0124] <Example 1> A magnetic sheet was produced using a manufacturing apparatus having the components shown in Fig. 13. The manufacturing method (including conditions and materials) of the magnetic sheet was the same as that of the first embodiment described above. Specific conditions and materials are shown below. Alloy ribbon: FT-3 (manufactured by Hitachi Metals, Ltd.) Alloy ribbon thickness: 16μm Alloy strip width: 60mm Number of layers: 4 Cracking roll pressure: 0.3MPa Magnetic sheet dimensions: 50mm x 50mm

[0125] <Example 2> A magnetic sheet was produced in the same manner as in Example 1.

[0126] <Evaluation> The AC relative magnetic permeability μr (128 kHz) of the magnetic sheet was evaluated. The evaluation results are shown in Table 1.

[0127] [Table 1]

[0128] As shown in Table 1, in Examples 1 and 2, the rate of change after 300 days (after 7200 hours) was within ±3.0%. On the other hand, in the magnetic sheet produced by the conventional manufacturing method (four layers of alloy ribbon laminated with an adhesive layer between two layers of resin film, and external force was applied from above the resin film to form cracks), the rate of change after 100 hours was 7% to 10%. The above results show that magnetic sheets with small changes in magnetic permeability were obtained in Examples 1 and 2.

[0129] The disclosures of Japanese Patent Application No. 2019-095278 filed on May 21, 2019 and Japanese Patent Application No. 2019-095279 filed on May 21, 2019 are incorporated herein by reference in their entirety. All documents, patent applications, and technical standards described herein are incorporated herein by reference to the same extent as if each individual document, patent application, and technical standard was specifically and individually indicated to be incorporated by reference. [Explanation of symbols]

[0130] 1, 1A, 1B, 1C, 1D, 1E, 1F: Release film 2, 2A, 2B, 2C: Tape 3: Adhesive layer 4, 4', 110: alloy strip 5: Cracking roll 6, 6A: Protective layer 6a, 6a1, 6a2: Protective film 6b: Adhesive layer 7: Cutter 8: Tray 9, 9', 9-1, 9-2: Crack 10a, 10d: Laminated member 10b, 10c: Laminate 10c4, 10e: first laminate 10c1, 10c2, 10c3: second laminate 11: Network cracking 20a, 20b, 20c: magnetic sheets 200: Power supply device 21: Power supply unit 22: Rectifier circuit 23: Switching circuit 24: Control circuit 25: Primary control coil 26: Resonant capacitor 201: Primary coil 300: Power receiving device 32: Rectifier circuit 33: Secondary battery 34: Battery control circuit 35: Secondary coil for control 41, 42, 43A, 43B, 44A, 44B, 45A, 45B, 46A, 46B, 47, 48, 49, 50: Guide rollers 60, 62: Dancer Roller 301: Secondary coil 111: Rolled body 112: Unwinding roller 114: Winding roller 120:Heating chamber 122: Heating plate 122S: 1st plane 130: Cooling room 132: Cooling plate 132S: 2nd plane 150: In-line annealing device

Claims

1. A magnetic sheet in which a plurality of alloy ribbons are laminated via adhesive layers, The alloy ribbon has a crack, The crack includes a linear crack, the longitudinal direction of the linear cracks is regularly formed in one direction as viewed from the lamination direction of the alloy ribbon and the adhesive layer, A magnetic sheet in which, when viewed from the stacking direction of the multiple alloy ribbons of the magnetic sheet, the position of the linear crack formed in a first alloy ribbon is different from the position of the linear crack formed in a second alloy ribbon among the multiple alloy ribbons.

2. The linear cracks include a plurality of first linear cracks formed regularly in one direction, and further include second linear cracks arranged at a distance in the longitudinal direction of the first linear cracks and formed regularly in one direction; The magnetic sheet according to claim 1 , wherein the first linear cracks and the second linear cracks are arranged at different positions in a direction perpendicular to the one direction.

3. The magnetic sheet according to claim 1 or 2, further comprising a network crack that connects the plurality of linear cracks to each other.

4. A magnetic sheet as described in any one of claims 1 to 3, wherein, when viewed from the stacking direction of the multiple alloy ribbons of the magnetic sheet, the position of a linear crack formed in a third alloy ribbon among the multiple alloy ribbons is different from the positions of linear cracks formed in the first alloy ribbon and the second alloy ribbon.

5. The magnetic sheet according to any one of claims 1 to 4, wherein the alloy ribbon is a nanocrystalline alloy ribbon.

6. The magnetic sheet according to any one of claims 1 to 5, further comprising a protective film provided on one or both end faces in a lamination direction of the plurality of alloy ribbons.

7. a cracking roll having a plurality of linear convex members regularly arranged on a circumferential surface of the alloy ribbon is pressed against the surface of the alloy ribbon to directly apply an external force thereto, thereby forming cracks in the alloy ribbon, thereby producing an alloy ribbon having cracks formed therein; A method for producing a magnetic sheet, the method including a step of laminating a plurality of alloy ribbons having cracks therein via an adhesive layer to produce a magnetic sheet in which a plurality of alloy ribbons are laminated, The alloy ribbon is a long alloy ribbon produced by continuously quenching a molten metal by roll quenching, The linear convex members arranged on the peripheral surface of the cracking roll are regularly formed in one direction relative to the rotation direction of the cracking roll, Each of the plurality of alloy ribbons includes a linear crack, A method for manufacturing a magnetic sheet, comprising a step of stacking the plurality of alloy ribbons such that, when viewed from the stacking direction of the plurality of alloy ribbons, the position of a linear crack formed in a first alloy ribbon and the position of a linear crack formed in a second alloy ribbon are different from each other.

8. The method for producing a magnetic sheet according to claim 7 , further comprising the step of forming a network crack that connects the plurality of linear cracks together after forming the plurality of linear cracks.

9. The magnetic sheet according to claim 7 or claim 8, further comprising a step of stacking the plurality of alloy ribbons such that, when viewed from the stacking direction of the plurality of alloy ribbons, the position of a linear crack formed in a third alloy ribbon among the plurality of alloy ribbons is different from the positions of the linear cracks formed in the first alloy ribbon and the second alloy ribbon.

10. The method for producing a magnetic sheet according to any one of claims 7 to 9, wherein the alloy ribbon is a nanocrystalline alloy ribbon.

11. The method for producing a magnetic sheet according to any one of claims 7 to 10, further comprising a step of adhering a protective film to one or both end faces in a lamination direction of the alloy ribbon.

Citation Information

Patent Citations

  • Continuous heat treating apparatus for nonferrous metal sheet

    JP1986227156A

  • Magnetic field shielding sheet for wireless chargers, method for manufacturing the same, and receiving device for wireless chargers using the same

    JP2015505166A

  • Magnetic sheet, electronic device using same, and method for manufacturing magnetic sheet

    WO2014157526A1

  • METHOD FOR PRODUCING Fe-BASED NANO-CRYSTAL ALLOY, AND METHOD FOR PRODUCING Fe-BASED NANO-CRYSTAL ALLOY MAGNETIC CORE

    WO2015046140A1